Effect of Moisture on Shape Memory Polyurethane Polymers for Extrusion-Based Additive Manufacturing - Garces, Irina T.; Aslanzadeh, Samira; Boluk, Yaman; Ayranci, Cagri (Materials, 2019)
Extrusion-based additive manufacturing (EBAM) or 3D printing is used to produce customized prototyped parts. The majority of the polymers used with EBAM show moisture sensitivity. However, moisture effects become more pronounced in polymers used for critical applications, such as biomedical stents, sensors, and actuators. The effects of moisture on the manufacturing process and the long-term performance of Shape Memory Polyurethane (SMPU) have not been fully investigated in the literature. This study focuses primarily on block-copolymer SMPUs that have two different hard/soft (h/s) segment ratios. It investigates the effect of moisture on the various properties via studying: (i) the effect of moisture trapping within these polymers and the consequences when manufacturing; (ii) and the effect on end product performance of plasticization by moisture. Results indicate that higher h/s SMPU shows higher microphase separation, which leads to an increase of moisture trapping within the polymer. Understanding moisture trapping is critical for EBAM parts due to an increase in void content and a decrease in printing quality. The results also indicate a stronger plasticizing effect on polymers with lower h/s ratio but with a more forgiving printing behavior compared to the higher h/s ratio.